2019
DOI: 10.2337/dc19-1113
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Clinical Burden of Nonalcoholic Steatohepatitis in Patients With Type 2 Diabetes in the U.S.

Abstract: Nonalcoholic steatohepatitis (NASH) is a progressive form of nonalcoholic fatty liver disease (NAFLD) and is strongly associated with type 2 diabetes mellitus (T2DM). Patients with both T2DM and NASH have increased risk for adverse clinical outcomes, leading to higher risk for mortality and morbidity. We built a Markov model with 1-year cycles and 20-year horizon to estimate the economic burden of NASH with T2DM in the U.S. RESEARCH DESIGN AND METHODS Cohort size was determined by population size, prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
144
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(153 citation statements)
references
References 36 publications
3
144
0
6
Order By: Relevance
“…2 However, it is probably higher because more than 90% of the studies used liver ultrasound for the diagnosis, which is less sensitive for intrahepatic triglyceride content than magnetic resonance-based imaging techniques. 3 Recently, Younossi et al 4 reported the significant burden of NASH in patients with T2DM in the United States. The overall prevalence of NAFLD was found to be >70%, or more than 18 million patients with T2DM and NAFLD.…”
mentioning
confidence: 99%
“…2 However, it is probably higher because more than 90% of the studies used liver ultrasound for the diagnosis, which is less sensitive for intrahepatic triglyceride content than magnetic resonance-based imaging techniques. 3 Recently, Younossi et al 4 reported the significant burden of NASH in patients with T2DM in the United States. The overall prevalence of NAFLD was found to be >70%, or more than 18 million patients with T2DM and NAFLD.…”
mentioning
confidence: 99%
“…Such patients have an increased risk for developing cirrhosis, and sometimes, hepatocellular carcinoma. A recent study showed that the prevalence of NAFLD in type 2 diabetes is approximately 60% [5]. Other studies from France and Turkey showed that the presence of fibrosis is high in these subjects [6,7].…”
Section: Introductionmentioning
confidence: 97%
“…Seven studies estimated the prevalence of advanced fibrosis in T2D patients with biopsy-proven NAFLD to be 17% (95% CI 7.2-34.8%) [18]. Among 18.2 million people in the US living with T2D and NAFLD, 6.4 million have NASH [19]. In T2D patients, the prevalence of advanced fibrosis is estimated to be 7.3-24.9% by FibroScan and 4.3-7.1% by magnetic resonance elastography (MRE) [20].…”
Section: Association Of T2d With Nash and Nafldmentioning
confidence: 99%